PENYALAHGUNAAN PIL KOPLO DI YOGYAKARTA: ANALISIS FAKTOR PENYEBAB DAN PERANAN BADAN NARKOTIKA NASIONAL PROVINSI (BNNP) DAERAH ISTIMEWA YOGYAKARTA DALAM PENCEGAHAN DAN PEMBERANTASAN - Janendra Shilla Wicaksono; Hendra Try Ardianto (Journal of Politic and Government Studies, 2026)
The misuse of “pil koplo” has become one of the narcotics-related problems that remains prevalent in the Special Region of Yogyakarta, particularly among adolescents and individuals of productive age. The circulation of these misused pharmaceutical drugs not only affects individual health but also creates broader social problems. Therefore, the active role of authorized institutions is required to supervise and combat the circulation of pil koplo. This study aims to analyze the factors that cause the misuse of pil koplo in Yogyakarta and to examine the role of the National Narcotics Agency of the Special Region of Yogyakarta Province (BNNP DIY) in the prevention and eradication of pil koplo misuse. This research uses a qualitative method with a descriptive approach. Data collection was conducted through in-depth interviews, observations, and documentation studies. The research subjects included officials from BNNP DIY, members of the community, as well as several informants related to the phenomenon of pil koplo misuse. The collected data were then analyzed to identify the causal factors and the forms of roles carried out by BNNP DIY in addressing this issue. The results of the study indicate that the misuse of pil koplo is influenced by several factors, including peer environment, easy access to pharmaceutical drugs, low public awareness of the dangers of drug misuse, and economic factors. In addressing this issue, BNNP DIY plays roles through various programs such as prevention, public socialization, community empowerment, rehabilitation for users, and law enforcement against illegal drug distribution networks. However, the implementation of these roles still faces several obstacles, such as limited resources, lack of inter-agency coordination, and low community participation. The conclusion of this study shows that addressing the misuse of pil koplo requires strong synergy between the government, law enforcement agencies, and the community so that prevention and eradication efforts can be carried out more effectively.